The hybrid Four‐CBS‐Domain KINβγ subunit functions as the canonical γ subunit of the plant energy sensor SnRK1. (15th May 2013) - Ramon, Matthew; Ruelens, Philip; Li, Yi; Sheen, Jen; Geuten, Koen; Rolland, Filip
Summary: The AMPK/SNF1/SnRK1 protein kinases are a family of ancient and highly conserved eukaryotic energy sensors that function as heterotrimeric complexes. These typically comprise catalytic α subunits and regulatory β and γ subunits, the latter function as the energy‐sensing modules of animal AMPK through adenosine nucleotide binding. The ability to monitor accurately and adapt to changing environmental conditions and energy supply is essential for optimal plant growth and survival, but mechanistic insight in the plant SnRK1 function is still limited. In addition to a family of γ‐like proteins, plants also encode a hybrid βγ protein that combines the Four‐Cystathionine β‐synthase (CBS)‐domain (FCD) structure in γ subunits with a glycogen‐binding domain (GBD), typically found in β subunits. We used integrated functional analyses by ectopic SnRK1 complex reconstitution, yeast mutant complementation, in‐depth phylogenetic reconstruction, and a seedling starvation assay to show that only the hybrid KINβγ protein that recruited the GBD around the emergence of the green chloroplast‐containing plants, acts as the canonical γ subunit required for heterotrimeric complex formation. Mutagenesis and truncation analysis further show that complex interaction in plant cells and γ subunit function in yeast depend on both a highly conserved FCD and a pre‐CBS domain, but not the GBD. In addition to novel insight into canonical AMPK/SNF/SnRK1 γ subunit function, regulation and evolution, we provide a new classification of plant FCD genes as a convenient and reliable tool to predict regulatory partners for the SnRK1 energy sensor and novel FCD gene functions.